Characterization of Pozzolanic Properties of Waste Glass as Partial Replacement of Cement - Nafisa, Tamanna (University Malaysia Sarawak, UNIMAS, 2015)
In recent years, the use of waste glass powder as a partial replacement of cement has introduced widely to reduce the amount of waste glass from the environment. Utilization of waste glass as cement replacement can contribute to reduce cement production that creates a greenhouse effect so that it can cut down the increasing environment pressure. The aims of this thesis were to investigate the pozzolanic characteristics of hardened cement paste inclusion with glass powder and the mechanical strength properties of mortar when cement is partially replaced with various sizes of glass powder and different level of replacement. In the experiment, the analysis was divided into two sections. One was microstructural analysis of cement paste incorporating with Glass Powder and another was mechanical strength behavior. Characterization of pozzolanicity in terms of hydration, development of hydrated products, identification of microstructure, chemical composition of hydrated products, structure of materials by means of hydration were analyzed through several experiments such as X-Ray Diffraction (XRD), Thermal Analysis (TGA and DTA), Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) in microstructural analysis section. The main products during hydration that are Calcium Silicate Hydrate (C-S-H) and Calcium Hydroxide (CH) were investigated to know the pozzolanic characteristics of samples. Mechanical properties in terms of compressive strength test was investigated in another section. For both microstructural analysis and mechanical strength analysis, soda lime glass powder with varying particle sizes in the range of 150-75μm, 75-38μm and <38μm were used as cement replacement with progressive curing of 1, 7, 21, 28, 56, 90 Days. Cement was replaced with 10%, 20%, 30% and 40% glass powder with constant water to cement ratio 0.45. In the FT-IR analysis, it was observed that cement paste with <38μm glass powder showed the strong peak of Calcium Silicate Hydrate (C-S-H) formation at higher stages for the replacement level of 10%, 20% and 30% with decreasing peak of another hydrated product Calcium Hydroxide (Ca(OH)2) which fulfills the characteristics of pozzolanicity in terms of hydration. A similar result was also found for X-Ray diffraction analysis. With the hydration of both C3S and C2S, the production of C-S-H increases with time. From thermal analysis, it can be concluded that the decomposition of CH is decreased with increasing the decomposition of C-SH simultaneously at 90 days for 75-38μm and <38μm glass powder. The microstructure analysis, SEM shows the formation of C-S-H (vide infra) is surrounded by many needle-like structures. It proves the development of C-S-H which makes the structure dense and compacted in nature gradually, while a part of cement is replaced by glass powder. Low Ca/Si ratio of cement paste supports the findings of microstructural analysis. From compressive strength, it can be concluded that the optimum percentage for clear glass powder as cement replacement is 10% by weight in mortar production with water to cement ratio 0.45. The compressive strength decreases with increasing replacement level and lower particle size shows the highest strength. Based on the results and observations, glass powder shows impressive results in the microstructure as well as compressive strength for <38μm glass powder. It can be concluded that the addition of waste glass can show better pozzolanic characteristics and enhance the performance of mechanical strength as cement replacement.